Design And Evaluation Of Artificial Catalysts That Possess Enzyme-Like Amidolytic Catalysis - Wong, Yoke Ming (2017)
In the present study, with the main goal of mimicking the amidase activity of protease,artificial polymer catalyst and peptide catalyst were designed and synthesized followed by various evaluations to investigate the validity of the design to possess enzyme-like amidolytic catalysis. Poly(N-isopropylacrylamide) microgel(NMG) has been developed by adding various functional groups to control surface charges, hydrophobicity, pKaand protein adsorption capacitybut seldom for enzyme mimics. Here, NMGsanchored with three types of functional groups were developed and studied aspolymercatalyststo hydrolyze amide bonds under evaluated mild conditions. Various evaluationstrategies were testedfor efficient hydrolysis activity on a p-nitroaniline-based substrate by using a colorimetric assay.